2011
DOI: 10.1523/jneurosci.6382-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Type-Specific Modulation of Feedback Inhibition by Serotonin in the Hippocampus

Abstract: Midbrain raphe nuclei provide strong serotonergic projections to the hippocampus, in which serotonin (5-HT) exerts differential effects mediated by multiple 5-HT receptor subtypes. The functional relevance of this diversity of information processing is poorly understood. Here we show that serotonin via 5-HT 1B heteroreceptors substantially reduces synaptic excitation of cholecystokinin-expressing interneurons in area CA1 of the rat hippocampus, in contrast to parvalbumin-expressing basket cells. The reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…44 In contrast, it has also been convincingly shown that inhibition of glutamate release by stimulation of 5-HT 1B Rs on axon collaterals from CA1 pyramidal cells, via CCK GABA interneurons and an inhibitory feedback loop, increase the firing of pyramidal CA1 neurons. 45 Moreover, recent data also indicate the presence of 5-HT 1B Rs on dendrites of hippocampal neurons, particularly granular cells of the dentate gyrus. 46 The current data imply that hippocampal 5-HT 1B Rs are of at least two types; 5-HT 1B Rs regulated by p11 and suppressing emotional memory processing, and other 5-HT 1B Rs that are independent of p11 and enhance emotional memory (Fig 5).…”
Section: Discussionmentioning
confidence: 98%
“…44 In contrast, it has also been convincingly shown that inhibition of glutamate release by stimulation of 5-HT 1B Rs on axon collaterals from CA1 pyramidal cells, via CCK GABA interneurons and an inhibitory feedback loop, increase the firing of pyramidal CA1 neurons. 45 Moreover, recent data also indicate the presence of 5-HT 1B Rs on dendrites of hippocampal neurons, particularly granular cells of the dentate gyrus. 46 The current data imply that hippocampal 5-HT 1B Rs are of at least two types; 5-HT 1B Rs regulated by p11 and suppressing emotional memory processing, and other 5-HT 1B Rs that are independent of p11 and enhance emotional memory (Fig 5).…”
Section: Discussionmentioning
confidence: 98%
“…When exogenously applied to cortical slices in vitro, 5-HT can modulate synaptic transmission (Winterer et al, 2011), depolarize interneurons via 5-HT2a receptors leading to IPSPs in pyramidal neurons (Gellman andAghajanian, 1993, 1994;Marek and Aghajanian, 1994), depolarize or hyperpolarize pyramidal neurons (Araneda and Andrade, 1991;Avesar and Gulledge, 2012), and decrease firing frequency adaptation in pyramidal neurons (Sheldon and Aghajanian, 1991). Optogenetic stimulation of ChR2-expressing DRN axons in vitro can excite hip- pocampal interneurons mediated by a mixed 5-HT 3 /glutamatergic mechanism, and this may lead to hyperpolarization of pyramidal neurons (Varga et al, 2009).…”
Section: Mechanisms Of Drn 5-ht Effectsmentioning
confidence: 99%
“…Moreover, given the selective innervation by CCK+ BCs in MEC, CCK may even act as a molecular switch at a larger level, deciding which PCs, and therefore which information-processing streams, may predominate in terms of relative activity levels at a given time. In addition, neuromodulators may not only directly regulate interneurons themselves in a specific manner, but may also act selectively on the excitatory inputs to some, but not all, interneuronal subtypes [75]. It is also possible that specific subgroups of PCs are regulated differentially by neuromodulatory systems, as indicated by, for example, a recent report that PCs in the somatosensory cortex can markedly differ in their ability for endocannabinoid mediated slow self-inhibition [76].…”
Section: Functional Implications and Outlookmentioning
confidence: 99%